O pacto nacional para alfabetização na idade certa (PNAIC) como prática inovadora de gestão de políticas públicas de educação básica: um estudo de caso - Lima, Amanda Barbosa Gaspar de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The National Plan for Literacy in the Right Age (PNAIC) as the innovative practices of the management of public policy of basic education: a case study The present work had as objective at investigating how the National Plan for Literacy in the Right Age (PNAIC) contributes to an innovation at school management practices as an example, a specific case, in the municipal network of Bauru. The methodology used was qualitative for being characterizing such as an ethnographic study, the data were systematized by descriptions and perceptions of coordinators who participated in this formation. From these results, the categories of analysis considered the contents of the formation, as well as the dimensions of the supporting practices to the management of literacy teachers as fundamental there in challenge to improve quality educational, mainly in the literacy process. The analyzes have shown the innovative practices in the implementation of some didactic sequences, as well as in the evaluation mode of the process of the literacy process. We can be concluded that, even without of continuity practices by the intermediary public agencies, the PNAIC has represented an innovation in the action of educational management of this relevant process of the formation of individuals, in this case, literacy student

O presente trabalho, que teve por objetivo investigar como a Formação do Plano Nacional para a Alfabetização na Idade Certa (PNAIC), contribui para a inovação das práticas de gestão escolar tomando como exemplo, um caso específico, na rede municipal de Bauru. A metodologia utilizada foi a qualitativa e, por se caracterizar como um estudo etnográfico, os dados foram sistematizados por meio de descrições e percepções dos coordenadores que participaram desta formação. A partir desses resultados, as categorias de análise consideraram aspectos dos conteúdos da formação, bem como dimensões das práticas de apoio à gestão dos professores alfabetizadores como fundamental no desafio de melhorar a qualidade educacional no processo de alfabetização, sobretudo. As análises evidenciaram as práticas inovadoras na implementação de algumas das sequências didáticas, bem como no modo de avaliação do processo de alfabetização. Podemos concluir que, mesmo com a falta de práticas de continuidade por parte dos órgãos públicos intermediários, o PNAIC tem representado uma inovação nas ações de gestão educacional desse relevante processo da formação dos indivíduos, nesse caso, alfabetizandos
Keywords: Escolas - Organização e administração; Professores - Formação; Inovações educacionais; Educação; Educational innovations - Brazil